Mechanical Properties of Barchip Polypropylene Fibre-reinforced Lightweight Concrete Made With Recycled Crushed Lightweight Expanded Clay Aggregate - Yew, Ming Kun; Yew, Ming Chian; Han Beh, Jing; Saw, Lip Huat; Lee, Foo Wei; Lee, Yee Ling (Frontiers in Materials, 2021)
Concrete is one of the broadly used construction materials in the construction industry. This research intends to recommend the replacement of conventional coarse aggregates with recycled lightweight expanded clay aggregate (LECA) which offers several advantages such as lightweight, low cost, and easily available. Lightweight concrete (LWC) offers numerous benefits; therefore, many researchers are using lightweight aggregate to produce lightweight structural composites concrete to compensate heavy loads by reducing the concrete self-weight due to lower density of lightweight concrete, improving in thermal properties and fire resistance, saving the cost of transportation and handling of precast units in the site. Different percentages (0, 0.15, 0.30 and 0.45%) of volume fraction of barchip polypropylene (BPP) fibre have been incorporated to improve the mechanical properties of lightweight aggregate concrete (LWA) concrete. In this study, the mixture of crushed lightweight expanded clay aggregate (CLECA) and barchip polypropylene (BPP) fibre have been used to achieve compressive strength between 28 to 37 MPa at 28-days with an oven-dry density ranged between 1900 to 2000 kg/m3. It is found that the inclusion of BPP fibres at an optimum volume fraction concrete enhances the compressive strength, splitting tensile strength and modulus of rupture. The compressive strength of the lightweight aggregate concrete containing 0.45% volume fraction of BPP fibre (CLLWAC-BPP0.45%) had achieved the highest compressive strength of 37 MPa at 28-days with a significant increment of about 31% compared to plain concrete. Hence, the findings of this research showed that the development of eco-friendly lightweight structural composites can be used as an alternative solution for infrastructure and marine fields application.